A review on detection and removal of raindrop using cameras - Shariah, Sawsan Kamel; Marhaban, Mohammad Hamiruce; Ramli, Abdul Rahman; Mohd Noor, Samsul Bahari (2005)
In this paper, a review for method applied for restoration of deteriorated images by using multiple cameras, and stereo video are presented. In outdoor environment, it is often the case that scenes taken by the cameras are hard to see because of adherent noises on the surface of the lens-protecting glass of the cameras. The visual effects of rain are complex. Rain consists of spatially distributed drops falling at high velocities. Each drop refracts and reflects the environment, producing sharp intensity changes in an image. A group of such falling drops creates a complex time varying signal in images and videos. In addition, due to the finite exposure time of the camera, intensities due to rain are motion blurred and hence depend on the background intensities. The techniques described in this paper can be used in a wide range of applications including Robot Vision, video surveillance, vision based navigation, video/movie editing and video indexing/retrieval.